Preparation method of MXene ion-selective membrane with continuous crown ether sites and application of MXene ion-selective membrane

CN122912707APending Publication Date: 2026-10-16HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611231031.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明为解决现有冠醚修饰二维膜存在的离子渗透率降低,锂富集效率低下的问题,进而提出一种具有连续冠醚位点的MXene离子选择性膜制备方法及MXene离子选择性膜的应用

Benefits of technology

[0015]本发明的有益效果是:本发明提供了一种使冠醚在MXene层间通道连续分布的方法,通过将4-甲酰苯并-15冠-5醚接枝在具有周期性重复羟基位点的聚乙烯醇上,使得冠醚在聚合物上连续分布。将这种具有空间连续分布特征的冠醚聚合物整合至MXene通道中,显著提高了氯化锂渗透率,并保持着对氯化镁的高效截留,有利于实现锂的快速提取,具体优点如下

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912707A_ABST
    Figure CN122912707A_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a MXene ion-selective membrane with continuous crown ether sites and application of the MXene ion-selective membrane, and relates to a preparation method of a MXene ion-selective membrane.The present application is used to solve the problems of existing crown ether modified two-dimensional membranes, such as low ion permeation rate and low lithium enrichment efficiency.The preparation method comprises the following steps: step 1, preparing 4-formyl-benzo-15-crown-5 ether grafted polyvinyl alcohol through an acetal reaction;step 2, preparing MXene nanosheets through a minimum strength layering method of lithium fluoride-hydrochloric acid;step 3, preparing a casting solution of 4-formyl-benzo-15-crown-5 ether grafted polyvinyl alcohol and MXene;step 4, using a film coating machine to coat the mixed solution on a nylon film to form a film; and step 5, drying the obtained MXene membrane at room temperature for 2h, and then vacuum drying the MXene membrane at 80 DEG C for 6h.The application belongs to the technical field of membrane material preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing an MXene ion-selective membrane and the application of the MXene ion-selective membrane, belonging to the field of membrane material preparation technology. Background Technology

[0002] In recent years, with the rapid expansion of the new energy industry and the continuous increase in demand for clean production, the global demand for lithium resources has been growing, making lithium resource development and capacity expansion an important development direction. my country's salt lake brines are rich in lithium resources. However, salt lake brines are usually accompanied by large amounts of magnesium ions (Mg). 2+ ), and lithium ions (Li + Lithium and magnesium ions are quite similar in hydration characteristics, ionic radius, and chemical properties, leading to a complex lithium-magnesium separation process and significant challenges in lithium resource enrichment. Therefore, developing highly selective lithium-magnesium separation materials for the efficient development of salt lake lithium resources is a crucial approach to ensuring my country's lithium resource supply, supporting the development of the new energy industry, and promoting energy structure transformation.

[0003] Two-dimensional MXene membranes possess regular and uniform interlayer channels, and their abundant surface functional groups provide favorable conditions for the introduction of functional units, thus they are often used as building blocks for precise ion separation membranes. Building upon this, introducing crown ether structures with specific cavity sizes and coordinated oxygen atoms can construct lithium-ion specific recognition and transport sites within the MXene interlayer. The selective coordination of lithium ions by the crown ether cavities enhances the lithium-magnesium transport differential, thereby improving the lithium-magnesium separation performance in brine. However, ions encounter an additional dehydration energy barrier when crossing crown ethers. Although the introduction of crown ethers improves selectivity, lithium-ion permeability further decreases, reducing lithium enrichment efficiency and limiting the practical application of crown ether-modified MXene membranes. Summary of the Invention

[0004] To address the problems of reduced ion permeability and low lithium enrichment efficiency in existing crown ether modified two-dimensional membranes, this invention proposes a method for preparing MXene ion-selective membranes with continuous crown ether sites and the application of MXene ion-selective membranes.

[0005] The technical solution adopted by the present invention to solve the above problems is as follows: The steps of the method for preparing an MXene ion-selective membrane with continuous crown ether sites according to the present invention include: Step 1: Under the catalysis of p-toluenesulfonic acid, 4-formylbenzo-15-crown 5-ether is grafted onto polyvinyl alcohol in dimethyl sulfoxide solvent to obtain a mixed solution. Unreacted small molecules are removed from the mixed solution by dialysis. Step 2: Add 2g of titanium aluminum carbide to a hydrochloric acid solution containing lithium fluoride and stir the reaction at 40°C for 24 hours. After the reaction is completed, repeatedly centrifuge and wash the generated black precipitate with deionized water until the pH of the supernatant reaches 6. Then, redisperse the washed black precipitate in deionized water and sonicate it. Centrifuge the resulting dispersion and collect the supernatant to obtain MXene colloidal solution. Step 3: Add the 4-formylbenzo-15-crown-5 ether-grafted polyvinyl alcohol treated in Step 1 to the MXene colloidal solution obtained in Step 2 to prepare a mixed solution; Step 4: Using a coating machine, the mixed solution obtained in step 3 is coated onto a nylon microfiltration membrane to obtain an MXene composite membrane with continuous crown ether sites. Step 5: Dry the MXene composite film obtained in Step 4 at room temperature, and then place it in a vacuum oven for thermal crosslinking and curing under vacuum conditions.

[0006] Furthermore, in step 1, the concentration of PVA is 10 mg / ml, the concentration of 4-formylbenzo-15-crown 5-ether is 20 mg / ml, the concentration of p-toluenesulfonic acid is 15 mg / ml, the reaction temperature is 80℃, and the reaction time is 12 h.

[0007] Furthermore, the molecular weight of polyvinyl alcohol is 146,000-186,000 Da.

[0008] Furthermore, the dialysis bag used in step 1 has a cutoff molecular weight of 3500 Da, and the dialysis time is 72 h.

[0009] Furthermore, the black precipitate from step 2 was redispersed in 200 ml of deionized water and ultrasonically cleaned for 20 min at 200 W to obtain an MXene colloidal solution.

[0010] Furthermore, in step 2, the MXene colloidal solution is centrifuged at 3500 rpm for 15 min, and the supernatant is collected to obtain the MXene solution; the obtained MXene solution is then centrifuged at 10000 rpm for 25 min to obtain the precipitate, and the precipitate is redispersed in a certain amount of deionized water, with the MXene solution concentration being 30 mg / ml.

[0011] Furthermore, the method for preparing the mixed solution of MXene and PVA-g-B15C5 in step 3 is as follows: PVA-g-B15C5 is added to the MXene solution and stirred continuously for 1 hour.

[0012] Furthermore, the coating method in step 4 is as follows: adjust the coating height of the coater to 100μm, and pour the obtained mixed solution of PVA-g-B15C5 and MXene onto a 0.22μm nylon microfiltration membrane for coating.

[0013] Furthermore, in step 5, the MXene composite membrane is dried at room temperature for 2 hours, and then thermally crosslinked in a vacuum drying oven at 80°C for 6 hours.

[0014] The MXene ion-selective membrane with continuous crown ether sites prepared by the method described in this invention can be applied in the field of lithium extraction from salt lake brine.

[0015] The beneficial effects of this invention are as follows: This invention provides a method for continuously distributing crown ethers in MXene interlayer channels. By grafting 4-formylbenzo-15-crown-5 ether onto polyvinyl alcohol with periodically repeating hydroxyl sites, the crown ether is continuously distributed on the polymer. Integrating this crown ether polymer with spatially continuous distribution characteristics into the MXene channels significantly improves lithium chloride permeability while maintaining efficient retention of magnesium chloride, which is beneficial for achieving rapid lithium extraction. Specific advantages are as follows: 1. This invention constructs a biomimetic transport channel with continuous lithium-ion recognition sites by continuously introducing crown ether functional units into the two-dimensional MXene interlayer channel. Compared with the problems of random distribution of functional sites and discontinuous ion transport paths in traditional membrane materials, this invention utilizes the specific coordination of crown ethers with lithium ions, enabling continuous coordination-hopping transport of lithium ions between adjacent crown ether sites, thereby reducing the resistance to lithium ion transmembrane transport and increasing the lithium ion permeation rate. While effectively suppressing magnesium ion transport, it significantly enhances the lithium-magnesium transport difference, which is beneficial to improving the selective enrichment efficiency of lithium ions in salt lake brine.

[0016] 2. This invention uses the regular interlayer channels of a two-dimensional MXene membrane as the ion transport framework, and integrates crown ether functional groups into the interlayer channels in an orderly manner through polymer chains, which can effectively regulate the interlayer spacing of MXene sheets and the channel microenvironment. Compared with membrane structures where crown ether sites are locally aggregated or randomly distributed, the continuous crown ether distribution formed by this invention can reduce the energy barrier for lithium ions to cross between adjacent recognition sites, making lithium ion transport within the membrane more continuous and efficient. At the same time, the layered structure of MXene can form both spatial and energy barriers for magnesium ions, which have larger hydration sizes and higher dehydration energy barriers, thereby achieving excellent lithium-magnesium separation performance while maintaining a high lithium ion flux.

[0017] 3. The MXene-crown ether ion-selective membrane structure constructed in this invention is stable, with the crown ether functional sites fixed within the interlayer channels by polymer chains. This overcomes the problems of easy loss, uneven distribution, and insufficient long-term operational stability of traditional physically doped functional molecules. Furthermore, this membrane material is prepared using a coating method, which is simple to operate and facilitates large-scale and continuous membrane fabrication, providing a material basis for the engineering application and large-scale promotion of lithium extraction membrane separation processes in salt lakes. Attached Figure Description

[0018] Figure 1 These are flowchart and digital photographic illustrations of Example 1; Figure 1 a is a schematic diagram of the process for preparing the MXene-PVA-C ion-selective membrane of Example 1 by the blade coating method; Figure 1 bc is a digital photograph of the MXene-PVA-C ion-selective membrane of Example 1; Figure 2 The X-ray diffraction patterns of the MXene film of Comparative Example 1, the MXene-C film of Comparative Example 2, the MXene-PVA film of Comparative Example 3 and the MXene-PVA-C film of Example 1, and the interlayer channel size of Comparative Example 1 and Example 1 are shown. Figure 3 These are schematic microscopic images of the MXene membrane and the MXene-PVA-C membrane in the comparative and examples; Figure 3 a is a scanning electron microscope image of the MXene film in Comparative Example 1. Figure 3 b is a scanning electron microscope image of the MXene-PVA-C film of Example 1; Figure 3 c is a cross-sectional transmission electron microscope image of the MXene film in Comparative Example 1. Figure 3 d is a cross-sectional transmission electron microscope image of the MXene-PVA-C film of Example 1; Figure 4 The grazing incidence X-ray wide-angle diffraction two-dimensional spectra of the MXene-PVA membrane of Comparative Example 3 and the MXene-PVA-C ion-selective membrane of Example 1, and the corresponding azimuth curves are shown. Figure 5 This is a schematic diagram of the permeation flux and lithium-magnesium selectivity in the comparative proportions and examples; Figure 5 a is a schematic diagram of the permeation flux of lithium chloride, sodium chloride, potassium chloride, calcium chloride and magnesium chloride for the MXene membrane of Comparative Example 1, the MXene-C membrane of Comparative Example 2 and the MXene-PVA-C membrane of Example 1. Figure 5 b shows the permeation flux of lithium chloride, sodium chloride, potassium chloride, calcium chloride, and magnesium chloride in the MXene-PVA membrane of Comparative Example 3. The inset shows the corresponding lithium-magnesium selectivity. Figure 6 This is a schematic diagram of the lithium-magnesium selectivity of the MXene membrane of Comparative Example 1, the MXene-C membrane of Comparative Example 2, and the MXene-PVA-C membrane of Example 1.

[0019] Example Example 1 The preparation method of the MXene ion-selective membrane with continuous crown ether sites described in this embodiment is carried out according to the following steps: Step 1: Under the catalysis of p-toluenesulfonic acid (10 mg / mL) and with dimethyl sulfoxide (DMSO) as solvent, 4-formylbenzo-15-crown-5 ether (4-FB15C5, 20 mg / mL) was grafted onto the molecular chain of polyvinyl alcohol (PVA, 146000-186000 Da, 10 mg / mL) to prepare 4-formylbenzo-15-crown-5 ether-grafted polyvinyl alcohol (PVA-g-B15C5); subsequently, the resulting mixed solution was dialyzed in a 3500 Da dialysis bag to remove unreacted small molecule impurities; Step 2: Add 2 g of titanium aluminum carbide (Ti3AlC2) to a 9 M hydrochloric acid (HCl) solution containing 2 g of lithium fluoride (LiF) and stir at 40 °C for 24 hours. After the reaction, repeatedly centrifuge and wash the generated black precipitate with deionized water until the pH of the supernatant reaches 6. Then, add water to the black precipitate and sonicate for 20 min. Centrifuge the sonicated MXene colloidal solution at 3500 rpm for 15 min and take the supernatant to obtain the MXene solution. Centrifuge the obtained MXene solution at 10000 rpm for 25 min to obtain the precipitate. Redisperse the precipitate in a certain amount of deionized water to obtain an MXene solution concentration of 30 mg / ml. Step 3: Add a certain mass of 4-formylbenzo-15-crown 5-ether grafted polyvinyl alcohol treated in Step 1 to the MXene solution prepared in Step 2 to prepare a mixed solution, wherein the mass of 4-formylbenzo-15-crown 5-ether grafted polyvinyl alcohol is 20% of MXene; Step 4: Adjust the coating height of the coater to 100 μm, pour the obtained mixed solution of PVA-g-B15C5 and MXene onto a 0.22 μm nylon microfiltration membrane, and use a coater to coat the mixed solution obtained in step 3 onto the nylon microfiltration membrane. This membrane is designated as the MXene-PVA-C membrane. Step 5: Dry the MXene ion-selective membrane obtained in Step 4 at room temperature for 2 h, and then place it in a vacuum oven for thermal crosslinking and curing at 80 °C under vacuum conditions for 6 h.

[0020] Example 2 Based on Example 1: In step 1, the molecular weight of polyvinyl alcohol is 13000-23000 Da, and the resulting ion-selective membrane is denoted as MXene-PVA-CL.

[0021] Example 3 Based on Example 1: In step 1, the molecular weight of polyvinyl alcohol is 89,000-98,000 Da, and the resulting ion-selective membrane is denoted as MXene-PVA-CM.

[0022] Comparative Example 1 (MXene membrane) Based on Example 1: 4-formylbenzo-15-crown-5 ether grafted polyvinyl alcohol (PVA-g-B15C5) was not introduced; that is, the preparation of PVA-g-B15C5 and its composite process with MXene in steps 1 and 3 were omitted. Instead, the MXene solution prepared in step 2 was directly used for coating. Specifically, the MXene solution was poured onto the surface of a 0.22 μm nylon microfiltration membrane, and coating was performed at a coating height of 100 μm. The membrane was then dried at room temperature for 2 h and treated in a vacuum oven at 80 °C for 6 h. The resulting membrane was designated as the MXene membrane.

[0023] Comparative Example 2 (MXene-C membrane) Based on Example 1: In step one, instead of grafting 4-formylbenzo-15-crown-ether onto polyvinyl alcohol, an equimolar amount of 4-formylbenzo-15-crown-5 is directly added to the MXene solution prepared in step 2.

[0024] Comparative Example 3 (MXene-PVA membrane) Based on Example 1: In step 1, polyvinyl alcohol does not undergo a grafting reaction.

[0025] Testing and Experiment Experiment 1: Figure 1 a represents a schematic diagram of the preparation method in Example 1. Figure 1 bc is a digital photograph of Example 1. As can be seen from the figure, the MXene-PVA-C ion-selective membrane has no defects on its surface and has good toughness.

[0026] Experiment 2: Comparative Examples 1, 2, and 3, and Example 1 were subjected to X-ray diffraction tests in both dry and wet conditions, and the results were as follows. Figure 2 The X-ray diffraction pattern shown is composed of... Figure 2It can be seen that the dry interlayer spacing of Comparative Example 1 is 13.7 Å and the wet interlayer spacing is 16.3 Å; the dry interlayer spacing of Comparative Example 2 is 14.1 Å and the wet interlayer spacing is 16.3 Å; the dry interlayer spacing of Comparative Example 3 is 15.8 Å and the wet interlayer spacing is 17.3 Å; and the dry interlayer spacing of Example 1 is 15.9 Å and the wet interlayer spacing is 17.3 Å. The thickness of MXene is 10 Å. Subtracting the MXene thickness, the dry free space of Comparative Example 1 is 3.6 Å and the wet free space is 6.6 Å; while the dry free space of Example 1 is 5.9 Å and the wet free space is 7.3 Å. Compared with Comparative Example 1 and Comparative Example 2, the swelling degree of Example 1 decreased by 58%, demonstrating good anti-swelling performance in aquatic environments.

[0027] Experiment 3: The cross-sectional morphology of Comparative Example 1 and Example 1 was observed using scanning electron microscopy and transmission electron microscopy. According to scanning electron microscopy, the thickness of both films was approximately 1.5 μm, while transmission electron microscopy revealed a uniform arrangement of MXene nanosheets in Comparative Example 1 and Example 1. Due to the intercalation effect of PVA-g-B15C5, the interlayer spacing of Example 1 was greater than that of Comparative Example 1.

[0028] Experiment 4: Grazing-incidence X-ray wide-angle scattering spectra were used to test Comparative Example 3 and Example 1, obtaining two-dimensional wide-angle scattering spectra, and further plotting the corresponding azimuth integral curves. Figure 4 It can be seen that the half-maximum width of the azimuth curve in Example 1 is significantly smaller than that in Comparative Example 3, indicating that the MXene nanosheets in Example 1 have a higher degree of orientational order. This result shows that, compared with PVA, PVA-g-B15C5 intercalation does not significantly disrupt the ordered stacking of MXene nanosheets.

[0029] Experiment 5: The ion fluxes of lithium chloride, sodium chloride, potassium chloride, calcium chloride, and magnesium chloride in Comparative Examples 1, 2, and 3 and Example 1 were tested, and the results were as follows: Figure 5 The diagram shown in ab. From... Figure 5 As can be seen from a, the fluxes of lithium chloride and magnesium chloride in Comparative Example 1 were 0.075 and 0.014 mol / (m²), respectively. 2 In Comparative Example 2, the fluxes of lithium chloride and magnesium chloride were 0.060 and 0.003 mol / (m³), respectively. 2 ·h), and Figure 5 b shows that the fluxes of lithium chloride and magnesium chloride in Comparative Example 3 were 0.053 and 0.014 mol / (m³), respectively. 2 ·h). Figure 5 The lithium chloride and magnesium chloride fluxes in Example 1 shown in Figure a are 0.120 and 0.0011 mol / (m²), respectively. 2Compared with Comparative Example 3, the lithium chloride flux of Example 1 was significantly increased, indicating that the continuous arrangement of crown ether sites in the MXene interlayer channel is conducive to promoting the rapid transport of lithium chloride.

[0030] Experiment Six: Based on the permeation fluxes of lithium chloride and magnesium chloride in Experiment Five, the lithium-magnesium permeation ratios of Comparative Example 1, Comparative Example 2, and Example 1 were calculated. Figure 6 It can be seen that the lithium-magnesium permeation ratio of Comparative Example 1 is 5.4, and that of Comparative Example 2 is 20.0. Compared with Comparative Example 2, the lithium-magnesium permeation ratio of Example 1 reaches 109.0, indicating that the continuous arrangement of crown ether sites in the MXene interlayer channels greatly improves the lithium-magnesium separation efficiency.

[0031] Lithium chloride and magnesium chloride permeation tests were performed on Examples 1-3 and Control Examples 1-3, and the lithium-magnesium separation ratio was calculated, as shown in Table 1: Table 1:

[0032] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent substitutions, and improvements made to the above embodiments without departing from the scope of the present invention, based on the technical essence of the present invention and within the spirit and principles of the present invention, shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing an MXene ion-selective membrane with continuous crown ether sites, characterized in that, The specific steps include: Step 1: Under the catalysis of p-toluenesulfonic acid, 4-formylbenzo-15-crown 5-ether is grafted onto polyvinyl alcohol in dimethyl sulfoxide solvent to obtain a mixed solution. Unreacted small molecules are removed from the mixed solution by dialysis. Step 2: Add 2g of titanium aluminum carbide to a hydrochloric acid solution containing lithium fluoride and stir the reaction at 40°C for 24 hours. After the reaction is completed, repeatedly centrifuge and wash the generated black precipitate with deionized water until the pH of the supernatant reaches 6. Then, redisperse the washed black precipitate in deionized water and sonicate it. Centrifuge the resulting dispersion and collect the supernatant to obtain MXene colloidal solution. Step 3: Add the 4-formylbenzo-15-crown-5 ether-grafted polyvinyl alcohol treated in Step 1 to the MXene colloidal solution obtained in Step 2 to prepare a mixed solution; Step 4: Using a coating machine, the mixed solution obtained in step 3 is coated onto a nylon microfiltration membrane to obtain an MXene composite membrane with continuous crown ether sites. Step 5: Dry the MXene composite film obtained in Step 4 at room temperature, and then place it in a vacuum oven for thermal crosslinking and curing under vacuum conditions.

2. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, In step 1, the concentration of PVA was 10 mg / ml, the concentration of 4-formylbenzo-15-crown 5-ether was 20 mg / ml, the concentration of p-toluenesulfonic acid was 15 mg / ml, the reaction temperature was 80℃, and the reaction time was 12 h.

3. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, Polyvinyl alcohol has a molecular weight of 146,000-186,000 Da.

4. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, The dialysis bag used in step 1 has a cutoff molecular weight of 3500 Da, and the dialysis time is 72 h.

5. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, The black precipitate from step 2 was redispersed in 200 ml of deionized water and ultrasonically cleaned for 20 min at 200 W to obtain an MXene colloidal solution.

6. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, In step 2, the MXene colloidal solution is centrifuged at 3500 rpm for 15 min, and the supernatant is collected to obtain the MXene solution. The obtained MXene solution is then centrifuged at 10000 rpm for 25 min to obtain the precipitate. The precipitate is redispersed in a certain amount of deionized water, and the concentration of the MXene solution is 30 mg / ml.

7. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, The method for preparing the mixed solution of MXene and PVA-g-B15C5 in step 3 is as follows: Add PVA-g-B15C5 to the MXene solution and stir continuously for 1 hour.

8. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, The coating method in step 4 is as follows: Adjust the coating height of the coater to 100μm, and pour the obtained mixed solution of PVA-g-B15C5 and MXene onto a 0.22μm nylon microfiltration membrane for coating.

9. The method for preparing an MXene ion-selective membrane with continuous crown ether sites according to claim 1, characterized in that, In step 5, the MXene composite membrane is dried at room temperature for 2 hours, and then thermally crosslinked in a vacuum drying oven at 80°C for 6 hours.

10. The application of an MXene ion-selective membrane with continuous crown ether sites prepared by the method of any one of claims 1 to 9, characterized in that, The MXene ion-selective membrane with continuous crown ether sites is applied in the field of lithium extraction from salt lake brine.